2004
DOI: 10.1111/j.1399-6576.2004.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Propacetamol and diclofenac alone and in combination for analgesia after elective tonsillectomy

Abstract: Combined treatment with propacetamol and diclofenac with the dosages used provided clinically only a minor advantage over monotherapy with propacetamol or diclofenac with respect to postoperative analgesia or the incidence of side-effects in adult tonsillectomy patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 13 publications
3
32
0
7
Order By: Relevance
“…Rømsing and his group in their systematic review reported that concurrent use of paracetamol and an NSAID was superior to paracetamol but not to NSAID [21]. In contrast, Hiller and his colleagues [22] reported that combined therapy with propacetamol and diclofenac offered no clinical advantage over monotherapy as regards postoperative analgesia in adult elective tonsillectomy patients. The difference between studies could be attributed to the study design, type of the procedure and selected population.…”
Section: Discussionmentioning
confidence: 95%
“…Rømsing and his group in their systematic review reported that concurrent use of paracetamol and an NSAID was superior to paracetamol but not to NSAID [21]. In contrast, Hiller and his colleagues [22] reported that combined therapy with propacetamol and diclofenac offered no clinical advantage over monotherapy as regards postoperative analgesia in adult elective tonsillectomy patients. The difference between studies could be attributed to the study design, type of the procedure and selected population.…”
Section: Discussionmentioning
confidence: 95%
“…1,11 Combination of two nonsteroidal anti-inflammatory drugs (diclofenac, naproxen, etodolac) with paracetamol was commonly used in our study, but when both are added the increase in efficacy is not much. 12 FDCs of diclofenac+serratopeptidase do not offer any particular advantage over the individual drugs despite the claim that serratopeptidase promotes more rapid resolution of inflammation. 13 Dicyclomine and paracetamol combination is highly irrational as paracetamol promotes sweating and thereby helps in heat dissipation.…”
Section: Discussionmentioning
confidence: 99%
“…19 In this study we used analgesic at optimum dose and regular basis in both control group and study group.…”
Section: Resultsmentioning
confidence: 99%